Seasonal Variability of Surface Ocean Currents in the Southern Java Offshore based on Global Reanalysis Data - Abdul Rahman; Lulut Alfaris; Andri Wahyudi; Anas Noor Firdaus; Ukta Indra Nyuswantoro; Nazish Laeiq (Universitas Negeri Gorontalo, 2025)
Surface ocean currents are a key component of marine circulation systems and play an important role in controlling physical and ecological processes in Indonesian sea. The Southern Java sea, which are directly connected to the eastern Indian Ocean, are characterized by dynamic surface circulation influenced by large-scale oceanic processes and seasonal monsoonal forcing. This study investigates the patterns and characteristics of surface ocean currents in the Southern Java sea using global ocean reanalysis data visualized through the Earth Nullschool platform. Seasonal variability was examined using representative monthly maps corresponding to the major phases of the Asian and Australian monsoon system, including January (West Monsoon), April (first transition season), July (East Monsoon), and October (second transition season). A descriptive analytical approach was applied to identify spatial and temporal variations in surface current direction and relative intensity across both coastal and offshore areas. The analysis reveals distinct seasonal differences in surface current behavior. During the East Monsoon period, surface currents exhibit stronger intensity and a more consistent alongshore orientation, reflecting enhanced wind-driven circulation and offshore transport. In contrast, the West Monsoon and transitional seasons are marked by weaker currents and greater directional variability, particularly in nearshore sea. These findings indicate that monsoonal wind forcing, combined with large-scale Indian Ocean circulation, is the primary driver of surface current variability in the study area. This study highlights the usefulness of reanalysis-based visualization for regional-scale oceanographic assessments in areas with limited in-situ observations. The results provide baseline information that supports regional oceanographic research and offers practical insights for marine resource management, fisheries, navigation, and coastal planning in the Southern Java sea